Preliminary Evidence for Correlation Between PASAT Performance and P3a and P3b amplitudes in progressive multiple sclerosis. - REILLY, RICHARD; KIISKI, HANNI; NOLAN, HUGH (My University, 2010)
Background. The no-go P3a event-related potential (ERP) is a measure of attentional engagement and the P3b is a measure of context updating. The aim of this study was to compare ERP topographies 1) to Paced Auditory Serial Addition Test (PASAT) results, 2) of visual and auditory P3a and P3b of PPMS patients vs. SPMS patients and 3) of both progressive subtypes to healthy controls. Methods. 30 subjects (10 PPMS, 10 SPMS and 10 age-matched controls) completed visual and auditory no-go P3a and P3b tasks while data were recorded from a 128-scalp channel EEG array. Data from scalp channels were converted into continuous interpolated images (incorporating the entire scalp and time). Topographical differences and correlations were then tested using statistical parametric mapping (SPM). Results. For the MS patients, PASAT score correlated significantly with parietal regions in the auditory P3b, auditory P3a and visual P3b conditions, and with central regions in the visual P3a condition. PPMS patients had significantly lower amplitude than SPMS patients in the auditory P3b condition over the parietal area. The control group had greater amplitude than the MS patients in all the P3 tasks, with the exception of the auditory P3b. Conclusions. These data suggest that PASAT performance and P3 ERPs correlate for MS progressive subtypes and that PPMS and SPMS in electrophysiologic responses differ during auditory P3b tasks.
PUBLISHED
EJoN-10-0246 PMID: 20666835 Article first published online : 28 JUL 2010
Keywords: Neuroscience; Multiple sclerosis;; Neuroscience; Next Generation Medical Devices